Empowering precision medicine: Insights from a national survey on pharmacogenomics knowledge, attitudes, and perceptions among community pharmacists in the UAE - Ammar Abdulrahman Jairoun; Sabaa Saleh Al-Hemyari; Moyad Shahwan; Mena Al-Ani; Mustafa Aal Yaseen; Mahmood H. Al-Aawad; Ghala Rashid Alnuaimi; B. Mahalakshmi (Elsevier, 2024)
Background: Community pharmacists are essential to pharmacogenomics implementation because they can help trainers, clinical advisors, and other medical professionals understand the importance of pharmacogenomics and encourage them to use it in their practice. This study is to evaluate the community pharmacists' understanding, attitudes, and perceptions of pharmacogenomics in the United Arab Emirates (UAE). Methods: Professionals employed at community pharmacies in Abu Dhabi, Dubai, and the Northern Emirates participated in a cross-sectional study design. From July 2023 to February 2024, five pharmacy students in their last year conducted the survey. The study team employed a structured questionnaire to collect data in addition to conducting in-person interviews. The study questionnaire comprised three distinct sections namely, demographic information, knowledge of pharmacogenomics concepts, and perceptions regarding pharmacogenomics. Results: A total of 586 pharmacists enrolled in the study. The average knowledge score regarding pharmacogenomics was 75.1 % with a 95 % confidence interval (CI) of [72.4 %, 77.7 %]. The average attitude score toward pharmacogenomics was 67.5 % with a 95 % CI of [66.3 %, 68.7 %]. Better pharmacogenomics knowledge among several groups: independent pharmacies (OR 1.7; 95 % CI 1.2-2.4), Pharmacists in Charge (OR 1.4; 95 % CI 1.3-2.02), pharmacists with 11-15 years of experience (OR 2.1; 95 % CI 1.4-4.2), graduates from international universities (OR 4.6; 95 % CI 1.6-12.9), and those who received training on pharmacogenomics (OR 11.9; 95 % CI 3.3-14.5). Similarly, better attitude scores were observed among independent pharmacies (OR 1.5; 95 % CI 1.1-2.1), Pharmacists in Charge (OR 1.5; 95 % CI 1.07-2.1), pharmacists with 16-20 years of experience (OR 2.1; 95 % CI 1.16-3.7), graduates regional universities (OR 1.47; 95 % CI 1.05-2.1), and those who received training on pharmacogenomics (OR 4.8; 95 % CI 3.2-7.3). Conclusion: The positive attitudes toward pharmacogenomics that we found in our research indicate that community pharmacists in the United Arab Emirates are beginning to realize the potential advantages of pharmacogenomics in terms of improving patient care. Policies ensuring the privacy and confidentiality of genetic information are also necessary in considering concerns about the availability of genetic test results to insurance companies and potential employers.